Human dental pulp stem cells modulate pro-inflammatory macrophages both through cell-to-cell contact and paracrine signaling - Maccaferri, Monia; Pisciotta, Alessandra; Carnevale, Gianluca; Salvarani, Carlo; Pignatti, Elisa (Frontiers in Immunology, 2024)
Macrophages play a key role in most of the inflammatory diseases such as Rheumatoid Arthritis (RA), but the mechanism underlying their pathogenesis is still under study. Among stem cells, human dental pulp stem cells (hDPSCs) have attracted attention due to their easy accessibility and immunomodulatory properties, making them a promising adjuvant therapy. Monocytes, isolated from buffy coats, were differentiated into pro-inflammatory M1 and anti-inflammatory M2 macrophages. Subsequently, they were cultured with hDPSCs either directly or via a cell-culture insert for 48 hours. Finally, they were analyzed for protein and gene expression. In our study, we have demonstrated that, hDPSCs, even without priming, are capable of reducing TNFα levels and enhancing IL-10 release in pro-inflammatory macrophages, both through direct contact and paracrine signaling. Furthermore, we found that their effects are more pronounced when in cell-tocell contact through the decrease of NF-kB and COX-2 expression and of CD80/PD-L1 colocalization. Our work highlights the immunomodulatory properties of hDPSCs on activated proinflammatory macrophages and the potential therapeutic role in inflamed tissue.